2020
DOI: 10.26803/ijlter.19.12.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lesson Plans from Rwandan Physics Teachers

Abstract: Lesson planning is a crucial roadmap guiding the teacher before the implementation of the lesson. In the current study, we aimed at reviewing pedagogical documents used by Rwandan physics teachers. We gathered 32 lesson plans related to optics topics from five teachers and analyzed them using the lesson plan analysis protocol (LPAP) and lesson plan evaluation form (LPEF) jointly. We have found that teachers do not prepare these documents as required by the newly introduced competence-based curriculum. Teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Practically teachers are concerned too much about time than the product of the lesson. A similar study was done in Rwanda, and Ndihokubwayo et al (2020a) found that teachers plan for low levels of Bloom's cognitive and affective taxonomy domains and do not follow effective inquiry techniques along the stages of the lesson activities.…”
Section: Pre-training Phasementioning
confidence: 83%
“…Practically teachers are concerned too much about time than the product of the lesson. A similar study was done in Rwanda, and Ndihokubwayo et al (2020a) found that teachers plan for low levels of Bloom's cognitive and affective taxonomy domains and do not follow effective inquiry techniques along the stages of the lesson activities.…”
Section: Pre-training Phasementioning
confidence: 83%
“…Learning preparation is a decision-making process that results from logically considering particular learning goals and objectives, namely behavioral changes and a sequence of actions that must be carried out to reach these goals by employing all available learning resources (Kobayashi, 2021). The final outcome of the decision-making process is the creation of papers including the aforementioned topics, so that these documents may be utilized as references and guides for the learning procedure (Ndihokubwayo et al, 2020;Nurtanto et al, 2021). The process of a plan must begin with the establishment of goals to be accomplished via a requirements analysis and full documentation, followed by the determination of the measures necessary to attain these objectives.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, problem-solving does not stop in the classroom; rather, its final stage and role lie in real life after school. This role should inform teachers how they should care about this approach during their planning (Ndihokubwayo et al, 2020) and teaching interaction.…”
Section: Discussionmentioning
confidence: 99%